The determination of some hormonal imbalance in the women with PCOS and verifying their effect on calcium homeostasis - Al-Shammary ‎, Zainab A.A.; Hani, Sally; Lena Ahmed AbdulAzeez Abdullah ‎ (University of Thi-Qar Journal of Science, 2025)
Polycystic ovarian syndrome is a common endocrinopathy in reproductive-aged women, associated with metabolic dysfunction influencing mineral metabolism and calcium regulatory pathway and affecting bone health. Thus, this study conducted to pinpoint specific hormonal abnormalities in PCOS women and to elevate their correlation with calcium homeostasis markers. A hundred specimen recruited from Iraqi women (50 PCOS patient and 50 serving as a control group (aged 18-40 years old). PCOS group was diagnosed according to standard Rotterdam criteria and were compared with controls without PCOS compatible in age and BMI. Blood samples were collected to quantify E2, LH, FSH, P.TH, Ca2+, and total testosterone by using hormone’s analyzer Addendum-Mini VIDAS apparatus (VIDAS) 12 mode l0, 1992. The PCOS group demonstrated higher LH, testosterone and calcium levels (4.96 ± 1.00) (0.64 ± 0.17) (10.37 ± 0.86) respectively, with decreased E2 and P.TH (55.12 ± 14.67) (25.08 ± 4.54) respectively when compared with control group, while FSH remained statistically unchanged. The data revealed a robust positive calcium-E2 correlation and an inverse E2-testesterone correlation implying a potential link between calcium homeostasis and ovarian steroidogenesis.